Evaluating the Moisture Susceptibility of Asphalt Mixtures Containing RCA and Modified by Waste Alumina - Sarah Khalid Ugla; Mohammed Qadir Ismael (Civil Engineering Journal, 2023)
The management of building and demolition waste is an important subject in the government's sustainability efforts. Today, recycling and reusing industrial waste and by-products is a topic of considerable relevance in every industry, but it is especially important in cement and concrete technology. Within the asphalt pavement sector, the necessity for environmentally friendly highway design and construction is at the top of the priority list. Nevertheless, due to the inferior behavior of the resulting recycled concrete aggregate (RCA) mixes, additional enhancement materials are needed. In this study, the effect of using alumina waste in the form of secondary aluminum dross (SAD) in the asphalt compacted specimens that contained RCA as coarse aggregate was discussed. The conventional limestone dust filler is replaced by SAD at rates of 10, 20, and 30% by filler weight in the control mix, and then the best percentage is used in mixtures containing RCA at rates of 25, 50, 75, and 100%. The experimental work includes volumetric properties by employing the Marshall design method, indirect tensile strength (ITS), and compressive strength. All the used percent of SAD enhanced the properties of the asphalt mixture; the tensile strength ratio (TSR) of the control mixture increased by 4.58%, 8.52%, and 7.64% for SAD rates (10, 20, and 30%), respectively. The best dosage of SAD was added to the mixture containing RCA at different specified rates. The maximum TSR (13.92%) was obtained at 25% RCA. The same steps were followed in the compressive strength test; adding SAD increased the index of retained strength (IRS) of the control mixture by 55.11, 13.42, and 9.13% for 10, 20, and 30%, respectively. Thereafter, the best dosage of 20% SAD was added to the hot mix asphalt (HMA) containing different RCA percents. The maximum IRS (17.43%) was also obtained at a 25% RCA. Doi: 10.28991/CEJ-SP2023-09-019 Full Text: PDF